2016
DOI: 10.1051/0004-6361/201527658
|View full text |Cite
|
Sign up to set email alerts
|

Detection and measurement of micrometeoroids with LISA Pathfinder

Abstract: The Solar System contains a population of dust and small particles originating from asteroids, comets, and other bodies. These particles have been studied using a number of techniques ranging from in-situ satellite detectors to analysis of lunar microcraters to ground-based observations of zodiacal light. In this paper, we describe an approach for using the LISA Pathfinder (LPF) mission as an instrument to detect and characterize the dynamics of dust particles in the vicinity of Earth-Sun L1. Launched on Dec. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…where P c ≈ 3.6 × 10 −8 N s [53]. Based on this simple estimation, one can compare the SNR obtained here with the one from the toy model (with the typical KAGRA parameters) discussed in Sect.…”
Section: Space-based Gw Detectorsmentioning
confidence: 76%
See 1 more Smart Citation
“…where P c ≈ 3.6 × 10 −8 N s [53]. Based on this simple estimation, one can compare the SNR obtained here with the one from the toy model (with the typical KAGRA parameters) discussed in Sect.…”
Section: Space-based Gw Detectorsmentioning
confidence: 76%
“…We can nevertheless, give some rough estimate to see, if light DM could be detected in these experiments. We follow the approach in [53] where they looked for micrometeroidal events at LPF which hit the spacecraft. In this reference, the relevant Fourier transform of a force acting on the target mass for a duration much shorter than the time resolution at t = 0 is justF = q R .…”
Section: Space-based Gw Detectorsmentioning
confidence: 99%
“…Another source of jitter is micrometeoroid or orbital debris impact, which causes a transfer of momentum from the impactor to the spacecraft. 40 In general, any release of energy through vibration would fall into this category, but again sources that are specifically due to microdynamics or thermal disturbances will be treated separately in this paper in Secs. 2.4 and 2.8.…”
Section: Microvibrationmentioning
confidence: 99%
“…The most substantial difference between the noise level in the various DoFs is in the amplitude of the S 4 term, which is substantially lower for the DoFs sensed by the interferometric system: x, η, and φ. In Thorpe et al (2016) it was shown that SNR of a simple impulse in the presence of this noise shape can be analytically computed as ρ = P i /P c , where P i is the amplitude of the momentum transfer in that DoF and P c is a characteristic threshold momentum given by:…”
Section: Impact Model and Sensitivitymentioning
confidence: 99%
“…This control system was designed to counteract disturbances on the spacecraft, including those caused by impacts from micrometeoroids. Shortly before LPF's launch, it was realized that data from the control system, if properly calibrated, could be used to detect and characterize these impacts and infer information about the impacting particles (e.g., Thorpe et al (2016)). Early results from the first few months of LPF operations suggested that such events could indeed be identified and were roughly consistent with the pre-launch predictions of their effect on the control system (e.g., Thorpe et al (2017)).…”
Section: Introductionmentioning
confidence: 99%